Utilization of Palm Broom Cutting Waste in Making Briquettes as a Potential Alternative Energy Source - Ade Nurul Hidayat; Dwi Irwati; Suhendra Suhendra; Dede Reno Suryana; Afra Nuraini (Universitas Islam Raden Rahmat, Malang, 2025)
The development of the industry continues to grow and produce products that continue to have useful functions. Production in the manufacture of goods has important industrial problems that must be managed. In the process of producing coconut brooms, there is coconut fiber waste from cutting, where the waste if left alone will become garbage and be thrown away. In the study using quantitative descriptive research methodology, namely by explaining how to make briquettes from coconut broom waste and then calculating the benefits that can be obtained from the waste if used as charcoal briquettes. Coconut broom waste will be used as briquettes that have economic value and can be used as potential economic value for the surrounding community. This study is a continuation of previous studies. This study has a novelty located in the raw material from coconut broom waste where waste that is usually thrown away and becomes unused waste, in this study we utilize it into a material that has economic value, namely made into briquettes. Furthermore, after the briquettes are made, the briquettes will be analyzed by looking at the Economic Feasibility Analysis, namely how much capital is needed and how much profit can be obtained, in this study the profit that can be obtained is IDR. 43,000.00 if we sell 10 packs for IDR. 10,000.00/pack.